EXPERIMENTAL AND FEASIBILITY STUDY OF THE UTILIZATION OF U-SHAPED HEAT PIPES FOR REDUCING AIR HUMIDITY IN HVAC SYSTEMS - Fadhil Fuad Rachman, Ragil Sukarno, and Nandy Putra (International Journal of Advanced Science and Technology, 2020)
Along with various activities carried out in the building, an HVAC system is needed to providea comfortable room in terms of temperature and humidity control for its occupants. Operatingan HVAC system requires a large amount of energy, which is around 30% of the total energyconsumption in the building, so it is important to reduce its energy consumption. To meet roomtemperature set point in conventional HVAC system, overcooling the fresh air and heating itback to achieve the needed room humidity is inevitable. This research has investigated the effectof utilization of U-shape heat pipe for reducing supply air humidity by reheating process beforeentering a conditioned room. The U-Shaped heat pipe experiments were varied using one rowand two rows with six heat pipe in each row. The inlet air temperature in the evaporator sectionwas varied of 35°C, 40 °C, and 45 °C, while the inlet air velocity varied of 1.5 m/s, 2.0 m/s and2.5 m/s. The results showed that the two-row of U-shaped heat pipes can reduce the relativehumidity as much of 21.31%. The highest effectiveness of 46 % was obtained when using the tworow U-shaped heat pipes at inlet air temperature of 35 °C and air velocity of 1.5 m/s. The highestenergy saving in reducing air humidity was 647 W, which was achieved with the two-row Ushaped heat pipes at inlet air temperature of 45 °C and air velocity of 2.5 m/s. With that amountof energy-saving value, the fastest payback time can be achieved by using the two rows U-shapedheat pipe for 0.5 years (six months), respectively.